EDUKASI BUDAYA TOPENG MALANGAN MELALUI MEDIA INTERAKTIF BOARD GAME - Al Hazmi Indrapasca Yoga; Alvanov Zpalanzani; Agus Sachari (Journal of Animation and Games Studies, 2020)
Traditional arts have become part of an area or even become the identity of it. This happenned in Malang, where Malang has a distinctive art called the Topeng Malangan. Topeng Malangan is a performance art that combines dance and puppet shows. The identity of the Topeng Malangan which is already very attached to Malang is inversely proportional to its popularity amongs Malang people. Therefore, an interesting and understandable educational media is needed to introduce Topeng Malangan into Malang people. Iterative design method is used in the design of this educational media. This iterative method can be used for finding a suitable game that can be played by families, because exploration, trials, and evaluations are involved in this design process.